2021
DOI: 10.1029/2020jf005970
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Lithologic Versus Tectonic Signals of River Profiles to Test Orogenic Models for the Eastern and Southeastern Carpathians

Abstract: Lithologic contrasts can be wrongly assigned as tectonic signals • Field and topographic evidence shows lithologic signals are prevalent in the East-10 ern Carpathians 11 • Tectonic forcing is successfully disentangled from lithology with systematic extrac-12 tion of relative steepness index

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 144 publications
(350 reference statements)
0
3
0
Order By: Relevance
“…Geomorphic indices were calculated using ArcGIS Pro and TAK (Forte & Whipple, 2018), k sn values were determined with a Θ ref = 0.45 following Kent et al (2017, 2021) and the profiler function. While the choice of reference concavity can impact the resultant k sn values, Gailleton et al (2021) demonstrated this is not significant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geomorphic indices were calculated using ArcGIS Pro and TAK (Forte & Whipple, 2018), k sn values were determined with a Θ ref = 0.45 following Kent et al (2017, 2021) and the profiler function. While the choice of reference concavity can impact the resultant k sn values, Gailleton et al (2021) demonstrated this is not significant.…”
Section: Methodsmentioning
confidence: 99%
“…Miller, Baldwin, & Fitzgerald, 2012; Ortega, Wohl, & Livers, 2013; Regalla et al, 2013; Snyder et al, 2000). However, landscape evolution modelling (Darling et al, 2020; Forte & Whipple, 2018; Forte, Yanites, & Whipple, 2016; Mitchell & Yanites, 2021; Perne et al, 2017) and field investigations at the landscape (Bernard et al, 2019; Zondervan, Stokes, et al, 2020) and catchment scale (Duvall, 2004; Gailleton et al, 2021; Kent et al, 2021; Peifer et al, 2020; Sklar & Dietrich, 2001; Whittaker et al, 2007) have increasingly investigated the importance of lithology on river incision and fluvial geomorphology. Yet, there are still uncertainties in how bedrock properties influence catchment scale erosion and how such characteristics can be effectively measured in the field.…”
Section: Introductionmentioning
confidence: 99%
“… . As discussed in Gailleton, Sinclair, et al (2021), the large eastward drop of sn E k by values between 470 and 480 is linked to a combination of differential lithology and recent tectonics. However, the relative magnitude of this reduction depends on the choice of We may be uncertain about the correct incision rule, and will therefore struggle to define a value of ref E  based on the physics of incision or sediment transport.…”
mentioning
confidence: 93%